A teaching module in research integrity and ethics for university students based on the IUPAC living-code approach - Sydnes Leiv K. (Chemistry Teacher International)
Through history, the relationship between science and society has changed, and today, science is almost totally integrated and an essential pillar in society. This development has changed the framework for scientific research and made it much more important to consider ethical issues related to both generation of knowledge and use of chemicals. However, such issues have barely been touched in traditional chemistry programs at university level until a few years ago, and there is therefore a need to introduce courses in these topics for university students. In this paper, the background for this need is outlined, and then a teaching module following the IUPAC layered approach is described. The module is based on a selection of key documents, dealing with research integrity and ethics, which are presented and discussed in lectures, workshops, and breakout groups. At the end, the course material is used by each student to write a code of conduct based on his or her working environment.